Development and validation of a nomogram for the prediction of lymph node metastasis within 2‐year postoperatively in cT1‐T2N0 oral squamous cell carcinoma. Issue 1 (13th October 2022) - Cheng, Aoming; Wang, Zhen; Yuan, Xiaohong; Liu, Huan; Cao, Wei; Wei, Wei; Chang, Shimin; Han, Zhengxue; Guo, Chuanbin; Feng, Zhien
Abstract: Background: The current neck management for early oral squamous cell carcinoma (OSCC) has always been a controversial issue. A comprehensive model is necessary for predicting an individual's metastasis risk and appropriate patient counseling. Methods: A nomogram for predicting 2‐year LNM in patients with cT1‐2N0 OSCC was developed and validated using clinicopathological data from 642 patients from 2000 to 2018 in four hospitals, China. Results: Three variables (pathology grade, depth of invasion, tumor‐infiltrating lymphocytes) were included in nomogram. C‐indices were 0.826 (95% CI: 0.786–0.866) and 0.726 (95% CI: 0.653–0.780) in the internal and external validation. Kaplan–Meier method found the 2‐year LNM rate of high‐risk group (35.8%) was much higher than that of the low‐risk group (14.5%). The nomogram model has an advantage over the 8th AJCC TNM stage in predicting the individual 2‐year LNM probability for early OSCC. Conclusion: Patients with low‐risk nomogram score may receive neck observation; those with high‐risk score should receive END.